Revealing the willingness to pay for income insurance in agriculture - Carlos Dionisio Pérez-Blanco; C. M. Gómez (Fondazione Eni Enrico Mattei (FEEM), 2015)
A stable agricultural income is often regarded as a way to achieve a better environmental performance in this sector. However, conventional income stabilization tools have been showing recently signs of exhaustion. Under this critical juncture, EU institutions have encouraged the expansion of agricultural insurance. With different degrees of public support, insurance systems against several risks have been successfully developed across the EU and have adopted increasingly comprehensive forms. Eventually, EU institutions have started to assess the development of a comprehensive income insurance framework. Income insurance covers a wider variety of risks and has higher costs than conventional single risk or combined insurance. This demands an in depth knowledge of farmers' Willingness To Pay (WTP) for this product. The following pages present a methodology that calculates the WTP for different degrees of income protection using a Revealed Preferences Model and the Certainty Equivalent theory. The methodology is applied in a drought prone area in southeastern Spain. Results show that WTP for income insurance in this area is higher than observed insurance premiums. This may play in favor of the development of sustainable income insurance systems, though additional evidence is required.
Keywords: Q14; Q17; Q18; Q20; 330; Insurance; Income; Agriculture; Certainty Equivalent; Revealed Preference Models